The Effect of Financial Compensation and Non-Financial Compensation on Employee Performance Through Motivation - Fatmawati Lestari; Siti Haerani; Wahda Rasyid (Hasanuddin Journal of Business Strategy, 2022)
The purpose of this study was to determine the effect of financial compensation and non-financial compensation on employee performance with motivation as an intervening variable at Makassar Social Welfare Education and Training Center (BBPPKS). The method of determining the sample in this study used a purposive sampling technique where the respondents amounted to 46 people. The data analysis technique used Smart PLS (Partial Least Square) software. The results of this study obtained that financial compensation has a significant effect on motivation, non-financial compensation has a significant effect on motivation, financial compensation has a significant effect on employee performance, non-financial compensation has no significant effect on employee performance, motivation has a significant effect on employee performance, financial compensation has a significant effect on employee performance. significant effect on employee performance through motivation, non-financial compensation has a significant effect on employee performance through motivation.